Outcomes of ophtalmologic surgical procedures of esotropia in children and adolescents - Kljaković-Avramović Tamara; Vukosavljević Miroslav; Avramović Siniša (Vojnosanitetski Pregled, 2008)
Background/Aim. Esotropia is the most common manifestation form of strabism accompanied by refraction deviations and amblyopia. The aim of this prospective study was to present the outcomes of surgical treatment of esotropia in children and adolescents. Methods. Within the period from January 1st 2006 to February 1st 2007 at the Clinic for Ophtalmology, Military Medical Academy, Belgrade a total of 25 patients with esotropia (34 eyes) and previously corrected refraction anomaly and treated amblyopia were operated on. The patients were 4-19-year of age. All of the patients were submitted to a complete ophtalmologic and orthoptic examination prior to the surgery, and a month, three months and six months after the surgery. The surgery was performed under general anesthesia. Out of the total number of the patients nine were operated on both eyes, while 16 patients on one eye with amblyopia or frequent esodeviation. Nine patients were submitted to retroposition of the inner straight muscle, two to myectomy of the outer straight muscle, while in 14 of the patients a combination of retroposition and myectomy was performed. The patients were divided into three groups according to the preoperative angle at the distance and followed-up accordingly after the surgery. Deviation angle at the distance in the group I was 18-25 DP, in the group II 26-35 PD, while in the group III it was 36-60 PD. Results. The most numerous, group I (12 patients; 48%), a month following the surgery showed angle reduction by 55.58%, after three months 63.25%, and after six months 63.92%. The group II consisted of 8 patients (32%) showed angle reduction by 70.75% a month following the surgery, by 76% after three months, and by 79.12% after six months. The group III (5 patients; 20%) showed angle reduction by 72.20% a month following the surgery, 79.20 after three months, and 80.12% after six months following the surgery. Conclusion. The best postoperative outcomes after a month, three and six months were obtained in the group of patients with the highest esodeviation angle at the distance solved by the surgery on both eyes. Timely surgical treatment befell into major precondition for developing and maintaining the elements of binocular vision in the operated on patients. .